Formation of professional competencies of future biology teachers based on STEM technologies - Symbat Ibadulla; Kalampyr Zhumagulova; Gulmira Zhussipova; Makhabbat Amanbayeva; Gani Issayev; Ardak Bostanova (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study developed an integrated pedagogical model incorporating Python programming, Arduino biosensors, and virtual reality (VR) applications aimed at biology teacher training. The 20-week study involved 124 participants (62 in the experimental group (EG) and 62 in the control group (CG)), with baseline competency levels assessed at the outset. Through collaborative projects, participants created technological applications integrated with biological content. Subject knowledge scores in the EG increased by 42.2% (from 22.3 ± 4.1 to 31.7 ± 3.2), compared to a 14.9% increase in the CG (from 22.1 ± 3.9 to 25.4 ± 3.7) (p